¿ES CONVENIENTE QUE PERÚ SUSCRIBA LA CONVEMAR? ARGUMENTOS PARA UNA RESPUESTA POSITIVA? - Herrada Guerrero, Víctor Domingo (Revista de Derecho, 2022)
This paper aims to describe the role of Peru in the Law of the Sea and provide an opinion on whether it is convenient for Peru to sign the United Nations Convention on the Law of the Sea of 1982 (UNCLOS). To do this, a brief historical review of the Law of the Sea is made, within which the role of Peru as a pioneer country in the thesis of the 200 nautical miles is highlighted. Subsequently, the circumstances in which UNCLOS originated and what this convention establishes are exposed. Finally, the current situation in Peru and what UNCLOS offers will be analyzed to provide a position on whether or not it is convenient for our country to sign this convention.